A systematic review and meta‐analysis of removable and fixed implant‐supported prostheses in edentulous jaws: post‐loading implant loss. Issue 2 (9th February 2015) - Kern, Jaana‐Sophia; Kern, Thomas; Wolfart, Stefan; Heussen, Nicole
Abstract: Objectives: The aim of this systematic review was to analyze post‐loading implant loss for implant‐supported prostheses in edentulous jaws, regarding a potential impact of implant location (maxilla vs. mandible), implant number per patient, type of prosthesis (removable vs. fixed), and type of attachment system (screw‐retained, ball vs. bar vs. telescopic crown). Material and methods: A systematic literature search for randomized‐controlled trials (RCTs) or prospective studies was conducted within PubMed, Cochrane Library, and Embase. Quality assessment of the included studies was carried out, and the review was structured according to PRISMA. Implant loss and corresponding 3‐ and 5‐year survival rates were estimated by means of a Poisson regression model with total exposure time as offset. Results: After title, abstract, and full‐text screening, 54 studies were included for qualitative analyses. Estimated 5‐year survival rates of implants were 97.9% [95% CI 97.4; 98.4] in the maxilla and 98.9% [95% CI 98.7; 99.1] in the mandible. Corresponding implant loss rates per 100 implant years were significantly higher in the maxilla (0.42 [95% CI 0.33; 0.53] vs. 0.22 [95% CI 0.17; 0.27]; P  = 0.0001). Implant loss rates for fixed restorations were significantly lower compared to removable restorations (0.23 [95% CI 0.18; 0.29] vs. 0.35 [95% CI 0.28; 0.44]; P  = 0.0148). Four implants and a fixed restoration in the mandible resulted in significantly higher implant loss rates compared to five or more implants with a fixed restoration. The analysis of one implant and a mandibular overdenture also revealed higher implant loss rates than an overdenture on two implants. The same (lower implant number = higher implant loss rate) applied when comparing 2 vs. 4 implants and a mandibular overdenture. Implant loss rates for maxillary overdentures on <4 implants were significantly higher than for four implants (7.22 [95% CI 5.41; 9.64] vs. 2.31 [1.56; 3.42]; P  < 0.0001). Conclusions: Implant location, type of restoration, and implant number do have an influence on the estimated implant loss rate. Consistent reporting of clinical studies is necessary and high‐quality studies are needed to confirm the present results.